2019
DOI: 10.1111/jdi.13183
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic invasive fungal disease in patients with type 2 diabetes mellitus from Southern China: Clinical features and associated factors

Abstract: Aims/Introduction: A retrospective study was carried out to investigate the clinical characteristics and associated factors for invasive fungal disease in patients with type 2 diabetes mellitus. Materials and Methods: Demographic and clinical data were recorded. Associated factors were analyzed by logistic regression analysis. Results: Invasive fungal disease was diagnosed in 120 patients with type 2 diabetes mellitus (prevalence, 0.4%). Yeast infection (56/120, 46.7%), including candidiasis (31/56, 55.4%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 56 publications
2
30
0
8
Order By: Relevance
“…The prognostic value of low serum albumin levels has been demonstrated not only for the development and complications of acute viral, bacterial, and fungal infections [ 95 ], but also for infectious complications in chronic conditions including malignant diseases [ 66 , 96 ], chronic inflammatory diseases [ 97 , 98 ], diabetes [ 95 ], hemodialysis [ 99 ], and solid organ transplantation [ 100 ]. In chronic infectious diseases, hypoalbuminemia is associated with disease reactivation/recurrence and secondary infections [ 101 , 102 , 103 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…The prognostic value of low serum albumin levels has been demonstrated not only for the development and complications of acute viral, bacterial, and fungal infections [ 95 ], but also for infectious complications in chronic conditions including malignant diseases [ 66 , 96 ], chronic inflammatory diseases [ 97 , 98 ], diabetes [ 95 ], hemodialysis [ 99 ], and solid organ transplantation [ 100 ]. In chronic infectious diseases, hypoalbuminemia is associated with disease reactivation/recurrence and secondary infections [ 101 , 102 , 103 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…In vitro studies have demonstrated that human IgM and immunoglobulin G (IgG) change the morphology of C. neoformans and that IgM inhibits titian-like cell formation, which can reduce virulence and the risk of disseminated disease [ 35 ] . Previous reports have described an association between hypogammaglobulinemia and increased risk for cryptococcal disease, including in HIV-infected patients [ 6 , 36–38 ] . Hypogammaglobulinemia—as a surrogate marker for immunodeficiency and nutritional status—can be a clinically helpful marker risk for cryptococcosis in HIV-uninfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM increases the risk for several fungal infections including Candida sp (21.6%), Cryptococcus sp (17.1%), and Aspergillus sp . (12.6%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%